Active integrated antenna with image reject mixer design - A. Rahim, Mohamad Kamal (IEEE, 2007)
Active integrated antenna with image reject mixer (AIA with IRM) operating at licenseless frequency of 2.4 GHz and intermediate frequency (IF) of 50 MHz is proposed. In this work, IRM is integrated with microstrip patch antenna on the similar substrate to attain size, weight and cost reduction. The suitable substrate that serves as the common platform for all integral components is FR-4 with dielectric constant of 4.7 and thickness of 1.6 mm. This AIA with IRM employs a different phase manipulation approach from the previous research in which the RF signal from the antenna is initially fed to 180deg rat race coupler instead of a 90deg coupler. Practically, this system is able to achieve image suppression with an isolation of approximately 20 dB between image and desired frequency with 7 dBm LO drive at 2.35 GHz. The integral components of AIA with IRM consist of 2-elements microstrip rectangular patch antenna, singly balanced schottky diode mixers, low pass filter, branch-line 90deg hybrid coupler, lumped element 90deg coupler and 180deg rat race coupler.